Belaboured Introductions: Inspired Reflections on the Introductory Course in Gender and Women’s Studies: Inspired Reflections: An Introduction - White, Melissa Autumn; Musial, Jennifer (Atlantis, 2016)
This introduction to Belaboured Introductions: Inspired Reflections on the Introductory Course in Gender, Women's and Sexuality Studies explores the major themes of our co-edited collection, which was motivated by our shared interests in the interplay of affective ecologies; storytelling; epistemologies and archives; seduction; austerity; labour and embodiment in the GWS classroom. Ultimately, our cluster contributes to what we see as a significant gap in the academic literature on the feminist scholarship of teaching and learning while provoking new questions about the role of the Introductory course in relation to field development and (re)constitution.